If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6z + -5 = 25 + 4z Reorder the terms: -5 + 6z = 25 + 4z Solving -5 + 6z = 25 + 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. -5 + 6z + -4z = 25 + 4z + -4z Combine like terms: 6z + -4z = 2z -5 + 2z = 25 + 4z + -4z Combine like terms: 4z + -4z = 0 -5 + 2z = 25 + 0 -5 + 2z = 25 Add '5' to each side of the equation. -5 + 5 + 2z = 25 + 5 Combine like terms: -5 + 5 = 0 0 + 2z = 25 + 5 2z = 25 + 5 Combine like terms: 25 + 5 = 30 2z = 30 Divide each side by '2'. z = 15 Simplifying z = 15
| 2x+6y=152 | | 396.2=-8.4x+455 | | (mx^2)-(4x)=m-5 | | 1/9y^2-5/7y | | 12+x=12-12x | | 12gh+3g(2h+9)+3g= | | 8r^2+11r+3=0 | | 1-x^2-3x=0 | | -3(u-8)=6u-48 | | (2x-3)(x-2)=10 | | 4(x+2)+3(2x-5)=13 | | y=8.3(10)+479 | | M-14=-50 | | 1/25(16-4q)=8/25q-4/5 | | 4(2p-7)-(p+7)-2(p+6)=-77 | | G+5=-12 | | 6p=4p+2 | | 5x+5y+13=0 | | 48/22-25/5 | | -4[(3p+3)-(6p-1)]=8(5-p)-2 | | 4(q-2)+2(q+4)=6 | | -9n-5=-10n-12 | | 4(4z+4)-16(z+3)=-z-7(z+8) | | 12x-12=9x | | 4(4z+4)-16(z+3)=-z-(z+8) | | 6+3(x)=0 | | v+16=2v-20 | | K=-7+15 | | 3+3+3(-2)= | | (Ln(x))=5+x | | ln(x)=5+x | | 3+3+3x=0 |